Sosialisasi Pengolahan Limbah Udang Sebagai Potensi Usaha Masyarakat Kelurahan Guntung - Diah Anugrah Dipuja; Al Akhbar Munassar; Humaira Azzahra; Lilis Octaviana (Pusat Riset dan Inovasi Nasional, 2023)
Guntung sub-district has the potential for shrimp farming. There is one pond called the brilliant shrimp pond. This shrimp mine itself can provide job opportunities for the community to create MSMEs regarding the use of shrimp. And with this shrimp farm, the Kukerta Guntung Team made an innovation by using shrimp as a natural artificial flavoring. The Kukerta Guntung Team service activity was held on August 19, 2023 at 10.00 WIB until it was finished. The method used in this service is to explain to the participants about the process of making it so that it becomes a natural flavor.